UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN SURUHAN (Peperomia pellucida L. Kunth) TERHADAP BAKTERI Shigella dysentriae - Destik Wulandari; Desi Purwaningsih (Fakultas Farmasi Universitas Setia Budi, 2016)
Shigella dysentriae is a bacteria that causes bacillary dysentery. This disease cause the patient to experience severe diarrhea. The efforts to overcome this disease is with using of antibiotics, but if the antibiotic is used for a long time can also to provide negative effects for humans. Therefore, needs a new antimicrobials that don't have negative effects for human, that is used of antimicrobial from plants. One of the plants that become candidate is suruhan (Peperomia pellucida L. Kunth). The purpose of this research is to know the antibacterial activity from the etanolic extract of the suruhan leaf (Peperomia pellucida L. Kunth) to against Shigella dysentriae bacteria by using dilution method. The method of this research is begins with the making of ethanol extract from suruhan leaf by maseration technique. The extracts then tested with concentrations of 100%, 80%, 60%, 40% and 20%. The antibacterial test using dilution method to find out Minimum Inhibition Concentration (MIC) and Minimum Kill Concentration (MKC). The results is show that MIC values can’t be determined because the mixture between the leaf extract and the Shigella dysentriae bacteria is very turbid. The value of MKC obtained by antibacterial activity from etanolic extract of the suruhan leaf on Shigella dysentriae bacteria was 40%.